Impaired peroxisomal beta-oxidation in microglia triggers oxidative stress and impacts neurons and oligodendrocytes - Tawbeh, Ali; Gondcaille, Catherine; Saih, Fatima-Ezzahra; Raas, Quentin; Loichot, Damien; Hamon, Yannick; Keime, Céline; Benani, Alexandre; Di Cara, Francesca; Cherkaoui-Malki, Mustapha; Andreoletti, Pierre; Savary, Stéphane (Frontiers in Molecular Neuroscience, 2025)
Microglia, the immune cells of the central nervous system, activate neuroinflammatory pathways in response to homeostatic disturbances, a process implicated in the pathogenesis of various neurodegenerative diseases. Emerging evidence identifies abnormal microglial activation as a causal factor at the onset of peroxisomal leukodystrophies, including X-linked adrenoleukodystrophy (X-ALD). This study investigates how primary peroxisomal deficiencies influence oxidative properties of microglia and examines the subsequent impact on neurons and oligodendrocytes. Using BV-2 microglial cells lacking ABCD1, ABCD2, or ACOX1, peroxisomal proteins that play key roles in the very-long-chain fatty acid beta-oxidation, we analyzed their response under basal condition and after stimulation by lipopolysaccharide (LPS). Transcriptomic analysis of the mutant microglial cells revealed numerous differentially expressed genes, particularly in redox-related pathways following LPS exposure. These changes are consistent with the increased production of reactive oxygen species (ROS) and nitric oxide (NO). Conditioned media (CM) from the mutant cells were then applied to cultures of neuron and oligodendrocyte cell lines. Exposure to CM from LPS-stimulated mutant microglial cells significantly increased apoptosis in both cell types. Furthermore, treated neurons exhibited a reduction in cell complexity and an increased ability to secrete neuropeptides. These findings demonstrate that peroxisomal impairments in microglia exacerbate inflammatory response and ROS/NO production, affecting the survival of neurons and oligodendrocytes, as well as neuronal morphology and function. This dysfunction might contribute to the early neurodegenerative events in X-ALD by triggering and sustaining neuroinflammatory cascades. Therapeutic strategies that target microglial activation and secretion profiles could hold promise in managing peroxisomal disorders such as X-ALD.